2022
DOI: 10.3390/audiolres13010003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Tinnitus Handicap Inventory and Tinnitus Functional Index as Treatment Outcomes

Abstract: Background: Tinnitus is an audiological disorder for which there are no objective measuring tools. Thus, many self-report questionnaires have been proposed to assess its severity. These questionnaires have been judged for their capacity to assess the tinnitus severity at baseline, their sensitivity to treatment-related changes (responsiveness), and their resolution. Methods: The most widely used questionnaires for clinical and research studies are the Tinnitus Handicap Inventory (THI) and the Tinnitus Function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…This questionnaire has also been used in medical practice and has been tested for validity. Therefore, apart from providing sound therapy and pharmacological therapy, the Tinnitus Handicap Inventory can be used as an evaluator to assess how severe the tinnitus symptoms are and can be used as a post-therapy evaluation [21].…”
Section: Discussionmentioning
confidence: 99%
“…This questionnaire has also been used in medical practice and has been tested for validity. Therefore, apart from providing sound therapy and pharmacological therapy, the Tinnitus Handicap Inventory can be used as an evaluator to assess how severe the tinnitus symptoms are and can be used as a post-therapy evaluation [21].…”
Section: Discussionmentioning
confidence: 99%
“…Since April 2021, participant also completed a new questionnaire, the Tinnitus Functional Index (TFI) [37][38] which was developed specifically to detect treatment-related changes of tinnitus. Fernández et al [22] demonstrated that both questionnaires were correlated (r = 0.74), behaved almost identically as evaluators of the tinnitus severity at baseline, and detected equally the changes related to the application of the EAE therapy.…”
Section: Tinnitus Outcomementioning
confidence: 94%
“…According to Jasterboff and Jastreboff [14], any type of sound that does not annoy, create discomfort, or damage hearing is better for tinnitus than silence. Nevertheless, customized sounds, personalized either to the tinnitus frequency [15][16][17][18] or the hearing thresholds [19][20][21][22], tend to provide more tinnitus relief.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, several variables are measured. the dependent variable is assessed objectively with the Tinnitus Handicap Inventory (THI) [11], [12], Tinnitus Primary Function Questionnaire (TPFQ) [13], and subjectively with the Visual analog scale (VAS T ) [14] while the independent variable is giving de tinnitus Song with a sound generator or noise generator. Confounding variables such as risk factors have been stratified and matched so that each group has confounding variables that are not much different.…”
Section: Methodsmentioning
confidence: 99%